From the foot-mouth reflex to the hand-mouth reflex a continuum of responses to Appendicular Compression Do reflexo pé-boca ao reflexo mão-boca: um continuum de respostas à Compressão Apendicular - Fleming S. Pedroso; Newra T. Rotta (Arquivos de Neuro-Psiquiatria)
We studied the mouth opening response to appendicular compression in two groups of children. This study was performed with the intention of testing the semiologic role of the act of mouth opening following stimulation of various regions, based on the hand mouth reflex of Babkin. Group I was formed by 33 normal children who underwent monthly follow up assessments since birth; and group II consisted of 50 children older than 6 months of age, known to have a neurologic deficit and a neuro-psychomotor development equivalent to that of a child in the first trimester of life. We observed that the normal mouth opening response in group I was more pronounced following compression of the hand and forearm when compared to compression of the arm (p<0.001). This response could persist for as long as the first 6 months of life. We were not able to elicit a mouth opening response following compression of the lower limb in this group. Among children from group II, we observed mouth opening responses to stimulation of all limb segments. Within the upper limb, the response was more pronounced following compression of the hand in comparison to the forearm (p<0.01), and forearm in comparison to the proximal arm (p<0.01). Stimulation of the foot was more effective in eliciting a mouth opening response when compared to equivalent stimulation of the lower leg (p<0.05). However, there was no statistical difference when responses to stimulation of the lower leg and thigh were compared. The presence of the previously unreported foot-mouth response may serve as an indicator of central nervous system compromise and could be associated with a poorer prognosis. We believe that our observations of the specific foot-mouth response patterns may serve as a marker of early neuro-psychomotor development dysfunction during childhood. Com a intenção de testar a importância semiológica da abertura da boca a estímulos em diferentes regiões, partindo do reflexo mão-boca de Babkin, foram estudadas as respostas de abertura da boca por compressão apendicular em dois grupos de crianças, sendo o grupo I constituído de 33 crianças normais acompanhadas desde o nascimento e revisadas ao final de cada mês e o grupo II constituído de 50 crianças com patologia neurológica com idade superior a 6 meses e cujo desenvolvimento neuropsicomotor (DNPM) fosse do 1° trimestre de vida. Observou-se que a evolução normal da resposta motora de abertura da boca no grupo I por compressão é mais eficiente na mão e antebraço do que no braço (p<0,001), podendo persistir durante o 1º semestre de vida. Não foi possível demonstrar esta resposta à compressão do membro inferior (MI). Nas crianças do grupo II, foi possível observar as respostas de abertura da boca aos estímulos em todos os segmentos apendiculares, sendo no membro superior (MS) o estímulo na mão mais efetivo do que no antebraço (p<0,01), no antebraço mais efetivo que no braço (p<0,01). Os estímulos no MI mostraram o pé mais efetivo do que a perna (p<0,05). Entretanto a eficácia do estímulo da perna em relação à coxa não foi estatisticamente significativo. A presença dessas respostas até agora não relatadas como pé-boca pode indicar maior severidade do comprometimento do sistema nervoso central, com pior prognóstico. Pensamos que estas observações possam ter especial interesse para os profissionais da reabilitação, constituindo mais um marcador de alterações neurológicas precoces no DNPM da criança.